2021
DOI: 10.4103/ijo.ijo_385_20
|View full text |Cite
|
Sign up to set email alerts
|

Ocular biometric measurements and optical coherence tomography parameters in children with refractive errors and emmetropia

Abstract: Purpose: The aim of this study was to estimate and compare the differences in ocular biometric measurements (OBMs), central macular thickness (CMT), and retinal nerve fiber layer thickness (RNFLT) between children with refractive errors and those with emmetropia. Methods: A cross-sectional observational study of 205 children (334 eyes) aged between six and 18 years consisting of four groups (emmetropia, hypermetropia, myopia, and astigmatism) was carried out. Best-corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[ 11 ] However, a few studies found an important association between the diagnosis of true strabismus and a positive family history of strabismus. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 ] The history of pre-term birth and a low birth weight (<2.5 kg) was observed in four (6.66%) and six (10%) children, respectively. One child with pre-term birth and a low birth weight who did not have strabismus at the first visit developed so (XT) at the third follow-up (18 months) [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] However, a few studies found an important association between the diagnosis of true strabismus and a positive family history of strabismus. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 ] The history of pre-term birth and a low birth weight (<2.5 kg) was observed in four (6.66%) and six (10%) children, respectively. One child with pre-term birth and a low birth weight who did not have strabismus at the first visit developed so (XT) at the third follow-up (18 months) [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, significant refractive error was defined as follows: for myopia, SER of ≥–0.5 D in one or both eyes; for pathological myopia, SER of ≥-6 D in one or both eyes; for hypermetropia, SER of ≥+0.5 in one or both eyes; for astigmatism, SER of ≥1.00 D in one or both eyes; and for emmetropia, SER between –0.5 and +0.5 in one or both eyes. [ 8 ] Dilated fundus examination was performed in all children, especially to look for macular scars, fibro-vascular proliferation, and macular drag, which can cause strabismus. These cases were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%